Ultra-small silver-copper nanocluster and preparation and application thereof
Ultra-small silver-copper nanoclusters synthesized by step-by-step reduction method are used for electrocatalysis, which solves the problems of harsh reaction conditions and safety hazards in the production process of cyclohexanone oxime, and achieves efficient and sustainable production of cyclohexanone oxime under mild conditions.
Patent Information
- Application Number
- CN202411760255.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The existing cyclohexanone oxime production process has harsh reaction conditions, high energy consumption, serious environmental pollution, and safety hazards, making it difficult to achieve sustainable production of cyclohexanone oxime under mild conditions.
Ultra-small silver-copper nanoclusters were synthesized by step-by-step reduction method. After forming a copper-yne precursor, silver-copper nanoclusters with particle sizes of 1.5-3 nanometers were obtained, which were used for electrocatalytic oxime synthesis.
It has achieved efficient catalysis of cyclohexanone oxime under mild conditions, excellent catalytic activity and stability, Faraday efficiency can reach 41%, selectivity to 100%, and the yield has only slightly attenuated after 8 cycles.
Smart Images

Figure HDA0005167451030000011 
Figure HDA0005167451030000021 
Figure HDA0005167451030000031
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental protection, and particularly relates to an ultra-small silver-copper nanocluster and preparation and application thereof. Background Art
[0002] Organic nitrogen chemicals are an indispensable part of modern society and have been widely used in life sciences, pharmaceutical industry, agriculture, textiles, chemicals and other fields. Oxime compounds, especially cyclohexanone oxime, are an important member of the family of organic nitrogen chemicals and are essential intermediates for the preparation of nylon-6 and industrial resins. It is estimated that the global production of nylon-6 will be close to 9 million tons by 2024, so the production demand for cyclohexanone oxime will expand accordingly. At present, 90% of the world's cyclohexanone oxime is produced by cyclohexanone (C6H 10 Cyclohexanone oxime is a kind of cyclohexanone oxime produced by the nucleophilic addition elimination reaction between cyclohexanone oxime (NH2O2) and hydroxylamine (NH2OH). However, the above chemical processes have harsh reaction conditions, high energy consumption and serious environmental pollution. At the same time, they are also faced with a series of potential safety hazards. In particular, the production of hydroxylamine requires NH3 (mainly prepared by the Haber process) and excess H2O2, and the reaction is carried out under high temperature and harsh conditions. In addition, hydroxylamine is unstable, and improper storage and use will cause some safety problems (such as explosion, etc.). Therefore, it is very necessary to develop a green and safe strategy to achieve the sustainable production of cyclohexanone oxime under mild conditions.
[0003] Electrochemical synthesis is currently emerging as a promising strategy for the sustainable production of value-added compounds and chemical raw materials by driving the reaction under mild conditions and utilizing renewable electricity. x ) The reduction reaction can convert NO x Upgrading waste to key chemical raw material NH3 has attracted increasing attention. It is worth noting that in most electrochemical NO x During the reduction reaction, the key intermediate *NH2OH (adsorbed hydroxylamine) is produced. Therefore, it is an attractive approach to synthesize cyclohexanone oxime by directly reacting the *NH2OH intermediate generated in situ with cyclohexanone.
[0004] At present, the development of high-performance electrosynthetic oxime catalysts focuses on pure copper nanomaterials. Although these materials have high activity, pure copper is easily oxidized or corroded under environmental conditions, which greatly reduces its catalytic activity and stability. Therefore, it is inevitable to use strategies such as alloy effect and confinement effect to synthesize highly active and stable copper-based materials. Summary of the invention
[0005] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing ultra-small silver-copper nanoclusters. The present invention adopts a step-by-step reduction method using Ag + and Cu + Reducibility and Cu + With Ag + Due to the significant difference in the ability to react with alkynes, a large number of silver-copper nanoclusters can be obtained by forming a copper alkyne precursor and then adding silver salt and a mild reducing agent in sequence. The preparation method is simple to operate and has good industrial application prospects.
[0006] Another object of the present invention is to provide ultra-small silver-copper nanoclusters prepared by the above method. The silver-copper nanoclusters obtained by the present invention have very small and uniform particle sizes, ranging from 1.5 to 3 nanometers, and the ultra-small particle size allows the surface of the silver-copper nanoclusters to have a large number of catalytic active sites.
[0007] Another object of the present invention is to provide the use of the ultra-small silver-copper nanoclusters in electrocatalytic oxime synthesis. The silver-copper nanoclusters obtained by the present invention have excellent catalytic activity and stability in the electrosynthesis of oxime.
[0008] The purpose of the present invention is achieved through the following solutions:
[0009] A method for preparing silver-copper nanoclusters comprises the following steps:
[0010] (1) dispersing a copper salt in an organic solvent to obtain a copper salt suspension;
[0011] (2) adding an alkynyl ligand solution and a silver salt solution to the copper salt suspension obtained in step (1) in sequence, stirring, adding a reducing agent solution dropwise, continuing to stir, separating the solid and the liquid, removing the organic solvent from the obtained supernatant, washing, and drying to obtain silver-copper nanoclusters.
[0012] The copper salt in step (1) is at least one of cuprous acetate, cuprous chloride, cuprous bromide, cuprous iodide, cuprous trifluoroacetate, tetraacetonitrile cupric tetrafluoroborate, and cuprous trifluoromethanesulfonate; preferably at least one of cuprous acetate and cuprous chloride.
[0013] The organic solvent in step (1) is at least one of toluene, dichloromethane, chloroform, carbon tetrachloride, 1,2-dichloroethane, tetrahydrofuran and ethyl acetate.
[0014] The amount of the organic solvent in step (1) is such that the concentration of the copper salt in the copper salt suspension is 0.01 to 0.5 mmol / mL.
[0015] The temperature for dispersing the copper salt in the organic solvent in step (1) is -10 to 5°C, preferably -10 to 3°C.
[0016] The alkynyl ligand in step (2) is at least one of phenylacetylene, 1-ethynylcyclopentane and 1-ethynylcyclohexane.
[0017] The silver salt in step (2) is at least one of silver acetate, silver trifluoroacetate, silver nitrate and silver tetrafluoroborate; preferably at least one of silver acetate, silver nitrate and silver tetrafluoroborate.
[0018] The solvent of the alkynyl ligand solution and the silver salt solution in step (2) is at least one of methanol, ethanol, acetonitrile, tetrahydrofuran, N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO).
[0019] The reducing agent in step (2) is at least one of sodium cyanoborohydride, tert-butylamine borane complex and diphenylsilane.
[0020] The solvent of the reducing agent solution in step (2) is at least one of methanol, ethanol and tetrahydrofuran.
[0021] The concentration of the alkynyl ligand in the alkynyl ligand solution in step (2) is 0.01-2 mmol / mL.
[0022] The concentration of silver salt in the silver salt solution in step (2) is 0.1-0.4 mmol / mL.
[0023] The concentration of the reducing agent in the reducing agent solution of step (2) is 0.001-0.25 mmol / mL.
[0024] The molar ratio of the silver salt in step (2) to the copper salt in step (1) is 0.2-4:1.
[0025] The molar ratio of the alkynyl ligand in step (2) to the copper salt in step (1) is 1-4:1; the molar ratio of the reducing agent to the copper salt in step (1) is 0.1-1:1, preferably 0.2-1:1.
[0026] The stirring time in step (2) is 1-4h.
[0027] The rate of the dripping in step (2) is 10-20 mL / h.
[0028] The rotation speed of the continued stirring in step (2) is 1200 rpm or above, preferably 1500-1800 rpm.
[0029] The time for continued stirring in step (2) is 15h to 24h; the temperature for stirring and continued stirring in step (2) is -10 to 5°C.
[0030] The solid-liquid separation in step (2) is centrifugation, wherein the centrifugal rotation speed is 6500 rpm or above, preferably 8000-9000 rpm.
[0031] The washing in step (2) is washing the solid with n-hexane at least three times.
[0032] The drying in step (3) is vacuum drying, and the drying temperature is 10-40°C, preferably 30°C.
[0033] The silver-copper nanocluster prepared by the method has a particle size of 1.5-3 nanometers and a uniform particle size.
[0034] The application of the above silver-copper nanoclusters in electrocatalytic oxime synthesis.
[0035] The application is specifically to use silver-copper nanoclusters as catalysts in the electrocatalytic reaction of co-reduction of nitrogen oxides and cyclohexanone to cyclohexanone oxime.
[0036] Mechanism of the present invention:
[0037] The present invention selects silver and copper from the same main group, which have good affinity and are easy to form alloy nanomaterials; + and Cu + Reducibility and Cu + With Ag + The significant difference in the ability to react with alkynes, Ag + It is easier to be reduced and become the core of AgCu ultra-small nanoparticles. + The copper is more likely to form a σ bond with the alkyne ligand and become a catalytic active site on the surface of the nanoparticle. Therefore, the copper alkyne precursor is first synthesized by the step-by-step reduction method. The formation of the copper alkyne precursor will make copper difficult to be reduced by the subsequent reducing agent. The addition of the reducing agent will then make the free Ag + It is reduced to zero valence and becomes the core of the nanoparticle, while Cu is located on the surface and connected to the alkynyl ligand, effectively protecting the silver core.
[0038] The alkynyl ligand selected in the present invention has a small radius and has bonding selectivity with silver and copper, thereby preventing the surface of the nanoparticles from being oxidized and agglomerated and not affecting the exposure of active sites, thereby preparing a highly active and highly stable electrosynthetic oxime catalyst.
[0039] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0040] (1) The preparation method is simple: the present invention adopts a step-by-step reduction method, and a large number of silver-copper nanoclusters can be obtained by adding a mild reducing agent to a mixed suspension containing a copper acetylene precursor and a silver salt, so it is easy to scale up for mass production.
[0041] (2) Ultra-small and uniform particle size: The silver-copper nanoclusters synthesized in the present invention have very small and uniform particle sizes, ranging from 1.5 to 3 nanometers. The ultra-small particle size allows the surface of the nanoclusters to contain a large number of catalytic active sites.
[0042] (3) Excellent catalytic performance: At a potential of -0.35 V, it has excellent performance in the co-reduction of NO and cyclohexanone to cyclohexanone oxime. The Faradaic efficiency of cyclohexanone oxime can reach 41%. At this potential, the selectivity of cyclohexanone oxime in the product can reach 100%. At the same time, the removal rate of cyclohexanone is as high as 95%. After 8 catalytic cycles, the Faradaic efficiency and yield of cyclohexanone oxime only slightly decay. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 (a)-(c) are transmission electron microscope (TEM) images of the silver-copper nanoclusters obtained in Example 1 at different magnifications.
[0044] Figure 2 The full X-ray photoelectron spectrum of the silver-copper nanoclusters obtained in Example 1 (a), the high-magnification X-ray photoelectron spectrum of the Ag 3d electron orbital (b), and the high-magnification X-ray photoelectron spectrum of the Cu 2p orbital (c).
[0045] Figure 3 The Faraday efficiency and yield (a) of cyclohexanone oxime, the product selectivity (b), the cyclohexanone removal rate (c) and the stability of the catalyst (d) of the silver-copper nanoclusters obtained in Example 1 in a flowing electrolytic cell with an electrolyte of 1 mol / L NaOH solution and a NO gas flow rate of 10 mL / min at different potentials.
[0046] Figure 4 In Example 1, silver-copper nanoclusters are used as catalysts, respectively 14 NO and 15 Mass spectrum of the electrosynthesized oxime products with NO as the N source.
[0047] Figure 5 The SEM image of the product obtained in Comparative Example 1 and the Faraday efficiency and yield of the electrosynthesized oxime at different potentials are shown.
[0048] Figure 6 The SEM image of the product obtained in Comparative Example 2 and the Faraday efficiency and yield of the electrosynthesized oxime at different potentials are shown.
[0049] Figure 7 (a)-(d) are TEM images of the silver-copper nanoclusters obtained in Examples 2, 4, 6, and 8, respectively.
[0050] Figure 8 The graphs are the Faraday efficiency and yield of the silver-copper nanoclusters obtained in Examples 2, 4, 6, and 8 at a potential of -0.35 V. DETAILED DESCRIPTION
[0051] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0052] Unless otherwise specified, the reagents used in the examples can be purchased from the market.
[0053] Example 1
[0054] (1) Disperse 0.3 mmol of cuprous acetate in 10 mL of dichloromethane at 0°C to form a suspension;
[0055] (2) The obtained stable solution was stirred at 0°C, and 0.12 mmol of diphenylsilane was added to 2 mL of methanol to prepare a reducing agent solution, and 0.6 mmol of 1-ethynylcyclohexane ligand was added to 3 mL of methanol to prepare a ligand solution, and 0.3 mmol of silver acetate was added to 3 mL of methanol to prepare a silver salt solution. The ligand solution and the silver acetate solution were added to the dichloromethane suspension of the copper salt in sequence, and the reducing agent was added dropwise after stirring for 2 hours. The dropping rate of the reducing agent solution was 12 mL / h. During the dropping process, the rotation speed was maintained at 1500 rpm. After the dropping was completed, the reaction was continued for 20 hours to obtain a crude product.
[0056] (3) The product obtained in step (2) was centrifuged at more than 8000 rpm to obtain a supernatant, and the organic solvent was removed by vacuum evaporation to obtain a solid. The solid was washed three times with 20 mL of n-hexane to remove by-products, and the solid was vacuum dried (30° C.) to obtain the final product.
[0057] Performance structure analysis
[0058] Figure 1 The transmission electron microscope (TEM) photos of the silver-copper nanoclusters in Example 1 at different magnifications can be clearly seen from the TEM images that the particle size of the synthesized silver-copper nanoclusters is very small, basically maintained between 1.5-2 nanometers, and the particle size is very uniform, and there are no silver-copper nanoparticles with too large or too small particle sizes.
[0059] Figure 2 The X-ray photoelectron energy (XPS) spectrum of the silver-copper nanoclusters of Example 1 shows that the 3d 3 / 2 and 3D 5 / 2 The electron binding energies of the orbitals are 374.53 eV and 368.53 eV respectively, and their electron binding energies are located in the Ag + and Ag 0 Between (Ag + and Ag0 3D 5 / 2 The electron binding energies of the orbitals are 367.3 and 368.68 eV respectively. The 2p 1 / 2 and 2p 3 / 2 The electron binding energies of the orbitals are 952.83eV and 933.08eV respectively, and their electron binding energies are located in the Cu + and Cu 0 Between (Cu + and Cu 0 2p 3 / 2 The electron binding energies of the orbitals are 933.3 eV and 932.6 eV, respectively), indicating that the valence states of silver and copper in the synthesized silver-copper nanoclusters are between 0 and +1, which is consistent with the characteristics of ultrasmall nanoparticles, but the valence state of Cu is almost +1, and the degree of reduction is very small, indicating that silver is almost all in the core of the nanoparticles, while Cu is almost all connected to the alkynyl ligands on the surface of the metal core of the nanoparticles, which is very different from traditional silver-copper nanoparticles. This indirectly shows that the particle size of the obtained clusters is very small, the metal atoms coordinated with the ligands on the surface are +1, and the internal metal atoms are 0, which is consistent with the characteristics of the clusters.
[0060] Figure 3 The performance test of the silver-copper nanoclusters of Example 1 in the electrosynthesis of cyclohexanone oxime in a flowing electrolytic cell with an electrolyte of 1 mol / L NaOH solution and a NO gas flow rate of 10 mL / min, wherein the silver-copper nanoclusters obtained in Example 1 are contained in 1 mg per square centimeter of the electrode surface. (a) is the Faraday efficiency and yield of cyclohexanone oxime electrosynthesized at different potentials. It can be seen from the figure that at a low potential of -0.35 V, the Faraday efficiency of cyclohexanone oxime reaches a maximum value of 41%, and the yield at this time can reach 2.96 mmol h -1 cm -2 (b) is the selectivity of the corresponding product. It can be seen from the figure that the selectivity of cyclohexanone oxime is 100% in the potential range of -0.15 to -0.55V. (c) shows the removal rate of cyclohexanone at different potentials. It can be seen from the figure that the removal rate of cyclohexanone reaches a maximum value of 95% at -0.35V. (d) shows that after 8 cycles of catalytic experiments, the silver-copper nanoclusters still have good catalytic activity, and the Faraday efficiency of cyclohexanone oxime is 33%, indicating that the stability of this catalyst is good.
[0061] Figure 4 The silver-copper nanoclusters of Example 1 were used as catalysts. 14 NO and 15 The mass spectrum of the electrosynthesized oxime product with NO as the nitrogen source shows that when 15 NO, the relative molecular mass of the product increased from 114.09 to 115.09. 15When NO is the nitrogen source, all its products are C6H 10 = 15 This indicates that the nitrogen element of the oxime in the system after reduction all comes from the added NO rather than other nitrogen sources in the environment.
[0062] Example 2
[0063] (1) Disperse 0.3 mmol of cuprous chloride in 10 mL of dichloromethane at 0°C to form a suspension;
[0064] (2) The obtained stable solution was stirred at 0°C, and 0.12 mmol of diphenylsilane was added to 2 mL of methanol to prepare a reducing agent solution, and 0.6 mmol of 1-ethynylcyclohexane ligand was added to 3 mL of methanol to prepare a ligand solution, and 0.3 mmol of silver acetate was added to 3 mL of methanol to prepare a silver salt solution. The ligand solution and the silver acetate solution were added to the dichloromethane suspension of the copper salt in sequence, and the reducing agent was added dropwise after stirring for 2 hours. The dropping rate of the reducing agent solution was 12 mL / h. During the dropping process, the rotation speed was maintained at 1500 rpm. After the dropping was completed, the reaction was continued for 20 hours to obtain a crude product.
[0065] (3) The product obtained in step (2) was centrifuged at more than 8000 rpm to obtain a supernatant, and the organic solvent was removed by vacuum evaporation to obtain a solid. The solid was washed three times with 20 mL of n-hexane to remove by-products, and the solid was vacuum dried (30° C.) to obtain the final product.
[0066] Example 3
[0067] (1) Disperse 0.3 mmol of cuprous acetate in 10 mL of dichloromethane at 0°C to form a suspension;
[0068] (2) The obtained stable solution was stirred at 0°C, and 0.12 mmol of sodium cyanoborohydride was added to 2 mL of methanol to prepare a reducing agent solution, and 0.6 mmol of phenylacetylene ligand was added to 3 mL of methanol to prepare a ligand solution, and 0.3 mmol of silver acetate was added to 3 mL of methanol to prepare a silver salt solution. The ligand solution and the silver acetate solution were added to the dichloromethane suspension of the copper salt in sequence, and the reducing agent was added dropwise after stirring for 2 hours. The dropping rate of the reducing agent solution was 12 mL / h. During the dropping process, the rotation speed was maintained at 1500 rpm. After the dropping was completed, the reaction was continued for 20 hours to obtain a crude product.
[0069] (3) The product obtained in step (2) was centrifuged at more than 8000 rpm to obtain a supernatant, and the organic solvent was removed by vacuum evaporation to obtain a solid. The solid was washed three times with 20 mL of n-hexane to remove by-products, and the solid was vacuum dried (30° C.) to obtain the final product.
[0070] Example 4
[0071] (1) Disperse 0.3 mmol of cuprous acetate in 10 mL of toluene at 0°C to form a suspension;
[0072] (2) The obtained stable solution was stirred at 0°C, and 0.12 mmol of diphenylsilane was added to 2 mL of acetonitrile to prepare a reducing agent solution, and 0.6 mmol of 1-ethynylcyclohexane ligand was added to 3 mL of acetonitrile to prepare a ligand solution, and 0.3 mmol of silver acetate was added to 3 mL of acetonitrile to prepare a silver salt solution. The ligand solution and the silver acetate solution were added to the dichloromethane suspension of the copper salt in sequence, and the reducing agent was added dropwise after stirring for 2 hours. The dropping rate of the reducing agent solution was 12 mL / h. During the dropping process, the rotation speed was maintained at 1500 rpm. After the dropping was completed, the reaction was continued for 20 hours to obtain a crude product.
[0073] (3) The product obtained in step (2) was centrifuged at more than 8000 rpm to obtain a supernatant, and the organic solvent was removed by vacuum evaporation to obtain a solid. The solid was washed three times with 20 mL of n-hexane to remove by-products, and the solid was vacuum dried (30° C.) to obtain the final product.
[0074] Example 5
[0075] (1) Dissolve 0.3 mmol of cuprous acetate in 10 mL of dichloromethane at 0°C to form a suspension;
[0076] (2) The obtained stable solution was stirred at 0°C, and 0.12 mmol of diphenylsilane was added to 2 mL of ethanol to prepare a reducing agent solution, and 0.6 mmol of 1-ethynylcyclohexane ligand was added to 3 mL of methanol to prepare a ligand solution, and 0.3 mmol of silver nitrate was added to 3 mL of methanol to prepare a silver salt solution. The ligand solution and the silver nitrate solution were added to the dichloromethane suspension of the copper salt in sequence, and the reducing agent was added dropwise after stirring for 2 hours. The dropping rate of the reducing agent solution was 20 mL / h. During the dropping process, the rotation speed was maintained at 1500 rpm. After the dropping was completed, the reaction was continued for 20 hours to obtain a crude product.
[0077] (3) The product obtained in step (2) was centrifuged at more than 8000 rpm to obtain a supernatant, and the organic solvent was removed by vacuum evaporation to obtain a solid. The solid was washed three times with 20 mL of n-hexane to remove by-products, and the solid was vacuum dried (30° C.) to obtain the final product.
[0078] Example 6
[0079] (1) Dissolve 0.3 mmol of cuprous acetate in 10 mL of dichloromethane at 0°C to form a suspension;
[0080] (2) The obtained stable solution was stirred at 0°C, and 0.12 mmol of diphenylsilane was added to 2 mL of methanol to prepare a reducing agent solution, and 0.6 mmol of 1-ethynylcyclohexane ligand was added to 3 mL of methanol to prepare a ligand solution, and 1.2 mmol of silver tetrafluoroborate was added to 3 mL of methanol to prepare a silver salt solution. The ligand solution and the silver acetate solution were added to the dichloromethane suspension of the copper salt in sequence, and the reducing agent was added dropwise after stirring for 2 hours. The dropping rate of the reducing agent solution was 12 mL / h. During the dropping process, the rotation speed was maintained at 1500 rpm. After the dropping was completed, the reaction was continued for 20 hours to obtain a crude product.
[0081] (3) The product obtained in step (2) was centrifuged at more than 8000 rpm to obtain a supernatant, and the organic solvent was removed by vacuum evaporation to obtain a solid. The solid was washed three times with 20 mL of n-hexane to remove by-products, and the solid was vacuum dried (30° C.) to obtain the final product.
[0082] Example 7
[0083] (1) Dissolve 0.3 mmol of cuprous acetate in 10 mL of dichloromethane at 0°C to form a suspension;
[0084] (2) The obtained stable solution was stirred at 0°C, and 0.3 mmol of diphenylsilane was added to 2 mL of methanol to prepare a reducing agent solution, and 0.6 mmol of 1-ethynylcyclohexane ligand was added to 3 mL of methanol to prepare a ligand solution, and 0.3 mmol of silver acetate was added to 3 mL of methanol to prepare a silver salt solution. The ligand solution and the silver acetate solution were added to the dichloromethane suspension of the copper salt in sequence, and the reducing agent was added dropwise after stirring for 2 hours. The dropping rate of the reducing agent solution was 12 mL / h. During the dropping process, the rotation speed was maintained at 1500 rpm. After the dropping was completed, the reaction was continued for 20 hours to obtain a crude product.
[0085] (3) The product obtained in step (2) was centrifuged at more than 8000 rpm to obtain a supernatant, and the organic solvent was removed by vacuum evaporation to obtain a solid. The solid was washed three times with 20 mL of n-hexane to remove by-products, and the solid was vacuum dried (30° C.) to obtain the final product.
[0086] Example 8
[0087] (1) Dissolve 0.3 mmol of cuprous acetate in 10 mL of dichloromethane at 0°C to form a suspension;
[0088] (2) The obtained stable solution was stirred at 0°C, and 0.12 mmol of diphenylsilane was added to 2 mL of methanol to prepare a reducing agent solution, and 0.6 mmol of 1-ethynylcyclohexane ligand was added to 3 mL of methanol to prepare a ligand solution, and 0.3 mmol of silver acetate was added to 3 mL of methanol to prepare a silver salt solution. The ligand solution and the silver acetate solution were added to the dichloromethane suspension of the copper salt in sequence, and the reducing agent was added dropwise after stirring for 4 hours. The dropping rate of the reducing agent solution was 15 mL / h. During the dropping process, the rotation speed was maintained at 1600 rpm. After the dropping was completed, the reaction was continued for 20 hours to obtain a crude product.
[0089] (3) The product obtained in step (2) was centrifuged at more than 9000 rpm to obtain a supernatant, and the organic solvent was removed by vacuum evaporation to obtain a solid. The solid was washed three times with 20 mL of n-hexane to remove by-products, and the solid was vacuum dried (20° C.) to obtain the final product.
[0090] Comparative Example 1
[0091] Comparative Example 1 is substantially the same as Example 1, except that in step (2), the silver salt solution is added before the ligand solution is added to the Cu salt suspension.
[0092] Figure 5 (a) is a TEM image of the product of Comparative Example 1, from which it can be seen that the material is severely agglomerated, and the overall particle size has reached the micron level and is no longer a nanomaterial. After the reaction is completed, the particle size of the silver-copper nanomaterial obtained is much larger than 2 mm or will quickly agglomerate and cannot be dispersed again. The reason is: although it is easier to interact with alkynes, the order of adding the Cu salt solution, the alkynyl ligand and the silver salt solution is also very important, and the order of adding the Cu salt-alkynyl ligand-silver salt solution must be followed to synthesize ultra-small silver-copper nanoparticles. If the silver salt is added before the alkynyl ligand, it will lead to the formation of a silver alkynyl precursor and the copper salt being reduced to nuclei, which will eventually lead to the surface ligands interacting with a large amount of silver, and the ability of silver to interact with alkynes is weaker than that of copper, so it is impossible to completely protect the silver-copper nanoparticles, resulting in irreversible agglomeration, and ultimately unable to form ultra-small and uniform silver-copper nanoclusters. (b) is when the electrolyte is 1 mol L -1 NaOH solution, NO gas flow rate was 10 mL min -1 The Faraday efficiency and yield of cyclohexanone oxime electrosynthesized at different potentials in a flow electrolytic cell, wherein each square centimeter of electrode surface contains 1 mg of the product obtained in Comparative Example 1. It can be seen from the figure that in the potential range of -0.15V to -0.55V, the maximum Faraday efficiency does not exceed 13%, and the maximum yield is 1.08mmol h -1 mg -1 , which is much lower than the performance of Example 1.
[0093] Comparative Example 2
[0094] Comparative Example 2 is substantially the same as Example 1, except that in step (2), the alkynyl ligand is 3,5-dimethoxyphenylacetylene.
[0095] Figure 6 (a) is a TEM image of the product of comparative example 2. It can be seen from the figure that the particle size of the material exceeds 200nm, and the silver-copper nanomaterial obtained after the reaction is completed cannot be effectively dispersed. The reason is: the ligand selection is wrong. Although the structure of 3,5-dimethoxyphenylacetylene is similar to phenylacetylene, cyclohexaneacetylene and cyclopentaneacetylene, its steric hindrance is much greater than the above three. Therefore, it cannot effectively protect the surface of the synthesized AgCu nanoparticles, which ultimately leads to excessive and uncontrollable growth of nanoparticles. (b) is the result of the reaction in an electrolyte of 1 mol L -1 NaOH solution, NO gas flow rate was 10 mL min -1 The Faraday efficiency and yield of cyclohexanone oxime electrosynthesized at different potentials in a flow electrolytic cell, wherein each square centimeter of electrode surface contains 1 mg of the product obtained in Comparative Example 2. It can be seen from the figure that in the potential range of -0.15V to -0.55V, the maximum Faraday efficiency does not exceed 9%, and the maximum yield is 0.7mmol h -1 mg -1 , far lower than the performance of Example 1
[0096] Figure 7 (a) to (d) are TEM images of Examples 2, 4, 6, and 8. It can be seen from the figures that although the experimental conditions of Examples 2, 4, 6, and 8 are different from those of Example 1, their TEM images show that the particle size of the synthesized silver-copper nanoclusters is about 1.5-3 nanometers, which is very close to the particle size of Example 1.
[0097] Figure 8 The silver-copper nanoclusters of Examples 2, 4, 6, and 8 were prepared in an electrolyte of 1 mol L -1 NaOH solution, NO gas flow rate was 10 mL min -1 The performance diagram of electrosynthesis of oxime at a potential of -0.35 V in a flow electrolytic cell, wherein 1 mg of silver-copper nanoclusters are contained per square centimeter of electrode surface. The data in the figure show that Examples 2, 4, 6, and 8 have good catalytic performance, with a Faradaic efficiency between 39% and 40%, and a yield of up to 2.85 mmol h -1 mg -1 -2.96mmol h -1 mg -1 .
[0098] In summary, Example 1 has the best catalytic performance, and its structure and performance are the most representative. In terms of structure, the particle size of the silver-copper nanoclusters is uniform and is between 1.5 and 2 nanometers. Generally speaking, the smaller the particle size, the more active sites can be exposed, and the performance of the nanomaterial will be better. After analyzing the electrosynthesized oxime products at different potentials, we found that it has the best performance for electrosynthesized oxime at a potential of -0.35 V. At this potential, the Faraday efficiency of the oxime reaches 41%, and the yield can reach 2.96 mmol h -1 mg -1 At the same time, the selectivity of oxime is over 100%, the removal rate of cyclohexanone is greater than 95%, and the Faraday efficiency of oxime is only slightly attenuated after 8 cycles of catalytic experiments at this potential, indicating that the stability of silver-copper nanoclusters is very good, and using them as electrosynthetic oximes has great application prospects and industrial value.
[0099] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing silver-copper nanoclusters, characterized in that: The following steps are involved: (1) dispersing a copper salt in an organic solvent to obtain a copper salt suspension; (2) adding an alkynyl ligand solution and a silver salt solution to the copper salt suspension obtained in step (1) in sequence, stirring, adding a reducing agent solution dropwise, continuing to stir, separating the solid and the liquid, removing the organic solvent from the obtained supernatant, washing, and drying to obtain silver-copper nanoclusters.
2. The method for preparing silver-copper nanoclusters according to claim 1, characterized in that: The copper salt in step (1) is at least one of cuprous acetate, cuprous chloride, cuprous bromide, cuprous iodide, cuprous trifluoroacetate, tetraacetonitrile copper tetrafluoroborate, and cuprous trifluoromethanesulfonate; The organic solvent in step (1) is at least one of toluene, dichloromethane, chloroform, carbon tetrachloride, 1,2-dichloroethane, tetrahydrofuran and ethyl acetate.
3. The method for preparing silver-copper nanoclusters according to claim 1, characterized in that: The amount of the organic solvent in step (1) is such that the concentration of the copper salt in the copper salt suspension is 0.01 to 0.5 mmol / mL; The temperature for dispersing the copper salt in the organic solvent in step (1) is -10 to 5°C.
4. The method for preparing silver-copper nanoclusters according to claim 1, characterized in that: The alkynyl ligand in step (2) is at least one of phenylacetylene, 1-ethynylcyclopentane and 1-ethynylcyclohexane; The silver salt in step (2) is at least one of silver acetate, silver trifluoroacetate, silver nitrate and silver tetrafluoroborate; The solvent of the alkynyl ligand solution and the silver salt solution in step (2) is at least one of methanol, ethanol, acetonitrile, tetrahydrofuran, N,N-dimethylformamide and dimethyl sulfoxide; The reducing agent in step (2) is at least one of sodium cyanoborohydride, tert-butylamine borane complex and diphenylsilane; The solvent of the reducing agent solution in step (2) is at least one of methanol, ethanol and tetrahydrofuran.
5. The method for preparing silver-copper nanoclusters according to claim 1, characterized in that: The concentration of the alkynyl ligand in the alkynyl ligand solution of step (2) is 0.01-2 mmol / mL; The concentration of silver salt in the silver salt solution of step (2) is 0.1-0.4 mmol / mL; The concentration of the reducing agent in the reducing agent solution of step (2) is 0.001-0.25 mmol / mL.
6. The method for preparing silver-copper nanoclusters according to claim 1, characterized in that: The molar ratio of the silver salt in step (2) to the copper salt in step (1) is 0.2-4:1; The molar ratio of the alkynyl ligand in step (2) to the copper salt in step (1) is 1-4:1; the molar ratio of the reducing agent to the copper salt in step (1) is 0.1-1:1, preferably 0.2-1:
1.
7. The method for preparing silver-copper nanoclusters according to claim 1, characterized in that: The stirring time in step (2) is 1-4h; The rate of the dropwise addition in step (2) is 10-20 mL / h; The stirring time in step (2) is 15 to 24 hours; The temperature of stirring and continuing stirring in step (2) is -10 to 5°C.
8. A silver-copper nanocluster prepared by the method according to any one of claims 1 to 7, wherein the particle size is 1.5-3 nanometers.
9. Use of the silver-copper nanoclusters according to claim 8 in electrocatalytic oxime synthesis.
10. The use according to claim 9, characterized in that: Silver-copper nanoclusters were used as catalysts in the electrocatalytic co-reduction of nitrogen oxides and cyclohexanone to cyclohexanone oxime.
Citation Information
Patent Citations
AuAgCu three-component alloy nano-cluster with controllable atom number and size and preparation method of AuAgCu three-component alloy nano-cluster
CN114888300A
Preparation method and application of copper nanoparticles regulated and controlled by gold and silver cluster surface modification
CN116393142A
Method for preparing ammonia by catalyzing NO through ultra-small copper nanoclusters
CN117646229A
Copper nanocluster and preparation method thereof
CN118290491A
Method for producing silver-copper composite nanoparticles
JP2013087341A